Determination of Missing Digit on the Year Number of Prasasti Sirah Keting - Prabowo, Agung; Sukono, Sukono (International Journal of Ethno-Sciences and Education Research, 2021)
In writing the inscription, several things need to be considered, one of which is the number of years. One example of an inscription that engraves the number of years up to thousands is the Sirah Keting Inscription. The condition of the inscription when it was found was worn, including the year number. According to J. L. A. Brandes and W. F. Stutterheim, the Sirah Kĕting inscription dates to 1026 Śaka, while according to the reading of Louis-Charles Damais, the year number is 1126 Śaka. The correctness of the differences in the reading of the number of years can be traced by using the Bratakesawa Tabulation, Damais Tabulation, Zeller Formual, and Sivaraman Formula. The four methods used gave the same results. The missing number in the hundreds position is 1 so that the number of years inscribed on the Sirah Keting Inscription is 1126 Saka or 1204 AD.